Effects of a catalytic volatile particle remover (VPR) on the particulate matter emissions from a direct injection spark ignition engine. - Xu, F; Chen, L; Stone, R (2011)
Emissions of fine particles have been shown to have a large impact on the atmospheric environment and human health. Researchers have shown that gasoline engines, especially direct injection spark ignition (DISI) engines, tend to emit large amounts of small size particles compared to diesel engines fitted with diesel particulate filters (DPFs). As a result, the particle number emissions of DISI engines will be restricted by the forthcoming EU6 legislation. The particulate emission level of DISI engines means that they could face some challenges in meeting the EU6 requirement. This paper is an experimental study on the size-resolved particle number emissions from a spray guided DISI engine and the performance of a catalytic volatile particle remover (VPR), as the EU legislation seeks to exclude volatile particles. The performance of the catalytic VPR was evaluated by varying its temperature and the exhaust residence time. The effect of the catalytic VPR acting as an oxidation catalyst on particle emissions was also tested. The results show that the catalytic VPR led to a marked reduction in the number of particles, especially the smaller size (nucleation mode) particles. The catalytic VPR is essentially an oxidation catalyst, and when post three-way catalyst (TWC) exhaust was introduced to the catalytic VPR, the performance of the catalytic VPR was not affected much by the use of additional air, i.e., no significant oxidation of the PM was observed.